Kepraktisan Media Pop Up Book Sub Tema Ayo Selamatkan Hewan dan Tumbuhan - Novitasari, Novitasari; Guntur, Muhammad; Bungawati, Bungawati; Wiratman, Arwan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study discusses the practicality of pop up book learning media on the material of let's save animals and plants in class VI MI Al-Ikhlas Balebo. The purpose of this study was to determine the specifications of pop up book learning media on the material of let's save animals and plants in class VI MI Al-Ikhlas Balebo; knowing the practicality of pop up book learning media on the material of let's save animals and plants in class VI MI Al-Ikhlas Balebo. This research uses a mixed method approach, namely by combining two qualitative methods and quantitative methods. This research was conducted at MI Al-Ikhlas Balebo, with grade VI teachers and 18 students as research subjects. Observation, interviews, questionnaires, and documentation are data collection methods. Qualitative and quantitative data analysis are two methods of data analysis. The results showed that pop up book learning media on the material of let's save animals and plants in a very practical category. Based on teacher interviews and student questionnaires, the practicality test resulted in a score of 85.6% with a very practical category. Pop up book teaching materials can be used in learning on this basis